Phytochemical analysis, anti-oxidant and anti-microbial activity of Acalypha indica leaf extracts in different organic solvents - Chekuri Sudhakar; Narendar Vankudothu; Shivaprasad Panjala; Nirmala Babu Rao; Roja Rani Anupalli (International Journal of Phytomedicine, 2016)
The herb Acalypha indica which belongs to Euphorbiaceae family has multiple medicinal properties which include anti-oxidant, anti-bacterial, anti-fungal, anti-inflammatory, antiulcer, anti-helmintic, anti-cancerous, anti-venom, and neuro-protective activity. The present study was designed to evaluate the phytochemical, antimicrobial and anti-oxidant activity of Acalypha indica leaves extracts in different solvent extractions like methanol, hexane, ethyl acetate and petroleum ether. Fresh leaves of the plant were collected and shade dried. Dried leaves were milled to obtain powder. Powder was subjected to soxhlet extraction using solvents and extracts were successively obtained. Phytochemical analysis was conducted following standard methods. Phytochemical analysis showed the presence of Alkaloids, Phenols, Saponins, Flavanoids and Amino acids. Leaf extract of methonal have shown the highest anti-oxidation capacity than hexane, ethyl acetate and petroleum ether. Anti-microbial activity has been performed on microbes like Bacillus sps, E.coli, Psuedomonas sps and Streptococcus sps. A highest value of zone of inhibition was found in methanol extract against E.coli. These results provide evidence that Acalypha indica leaf extract possesses vital phytochemicals, antimicrobial and antioxidant properties. Hence this plant can be studied further for drug analysis for finding potent medicines for diseases.